Impact of neurological disorders occurring in neurodegenerative diseases on the conversation process and patients' quality of life - Katarzyna Mielniczek; Aleksandra Kowalska; Katarzyna Jóźwik; Marta Lipiec; Diana Dołomisiewicz (Journal of Education, Health and Sport, 2022)
Introduction : Dialogue, or conversation, is the ability to speak as well as listen.  It plays a very important role in interpersonal relations.Speech disorders are a group of of disorders that includes various types of speech production difficulties. Speech production depends on the coordination of several motor acts: respiration, phonation, articulation, resonance and prosody. Phonation is the complex activity of producing sound by vibration of the vocal cords.  Resonance is the amplification of sounds at specific frequencies through vibration in the chest, throat and sinuses. Prosody includes a set of phonetic features, such as tone, loudness, tempo, and the overall timbre of speech, which are designed to intended to preserve the meaning and character of speech. Disruption of any of these related elements results in motor speech disorders.